Toxicity of Shirazi thyme, Zataria multiflora essential oil to the tomato leaf miner, Tuta absoluta (Lepidoptera: Gelechiidae). (27th December 2018) - Chegini, Samira Goudarzvande; Abbasipour, Habib; Karimi, Jaber; Askarianzadeh, Alireza
Abstract: The tomato leafminer, Tuta absoluta (Meyrick) is a destructive pest of tomato, potato and other solanaceous crops of economic importance. One of the primary tools in its management is the use of conventional synthetic insecticides; however, this overreliance on synthetic insecticides quickly leads to the problem of insecticide resistance. In recent years, essential oils (EOs) of medicinal plants have received much attention as pest control chemical agents. If found, active compounds that are less persistent will be beneficial for both the environment and agricultural product consumers. In the current study, we studied the fumigant toxicity of EO of the Shirazi thyme, Zataria multiflora Boiss on the eggs, the second larval instars and adults. We analysed the composition of the EO by gas chromatography–mass spectrometry. The major component in the oil was thymol (33.52%). The EO showed strong adulticidal, larvicidal and ovicidal activity. Results show that by increasing the oil concentration, mortality will increase. By Probit analysis, the LC50 values for eggs, second larvae (inside leaf, outside leaf) and adults were 60.26, 4.44, 1.26 and 1.38 µl/L air, respectively. The EO of Z. multiflora may be suitable as a fumigant, because of its high volatility and safety.